2021
DOI: 10.3389/fmed.2021.647679
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Social Responsiveness Toward Corona Virus Disease 2019 (COVID-19) Among Chinese Medical Students—Thoughts on Medical Education

Abstract: Purpose: To assess knowledge, attitudes, and social responsiveness toward COVID-19 among Chinese medical students.Methods: Self-administered questionnaires were used to collect data from 889 medical students in three well-known Chinese medical universities. The questionnaire was comprised of three domains which consisted of demographic characteristic collection, seven items for knowledge, and eight items for attitudes and social responsiveness toward COVID-19. Data from different universities were lumped toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Some studies have shown that before entering medical college, the mental health levels of medical students are the same or higher than those of their peers [ 50 , 51 ], but after starting medical school their mental health can deteriorate [ 52–54 ]. Relevant research has suggested that newly enrolled medical students have excessive expectations for professional happiness, and could be easily affected by interventions [ 55 ]. Senior students are particularly likely to suffer from burnout [ 53 , 56 , 57 ], which is related to the level of stress they experience.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that before entering medical college, the mental health levels of medical students are the same or higher than those of their peers [ 50 , 51 ], but after starting medical school their mental health can deteriorate [ 52–54 ]. Relevant research has suggested that newly enrolled medical students have excessive expectations for professional happiness, and could be easily affected by interventions [ 55 ]. Senior students are particularly likely to suffer from burnout [ 53 , 56 , 57 ], which is related to the level of stress they experience.…”
Section: Discussionmentioning
confidence: 99%
“…In China, medical resources are unevenly distributed, such as resources of equipment and talents, and are mainly concentrated in developed cities and high-level hospitals ( 37 ). We considered the medical curiosity as the main cause of the significant difference in the knowledge toward COVID-19 between the participants from tertiary and basic-level hospitals, which has been reported in recent studies ( 38 , 39 ). Interestingly, studies of educational psychology revealed that the trait of curiosity is positively associated with academic achievement and the educational process may affect the state of curiosity of medical students ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, medical education in China has emphasized the importance of treatment more than prevention for a long time. Specifically, the proportion of public health courses is relatively small in the current system of clinical medical education, and there are few opportunities for clinical medical students to participate in public health practice (22,42). As a result, many medical workers were infected unexpectedly in the early stage of the epidemic, due to the insufficient public health literacy, especially in the basic-level hospitals (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicated that both academic education and short-term training help increase the experimental competencies of p-lab staff, who also subjectively believe that personnel and staff training are crucial determinants to improving p-lab capacity. Given the above, the relevant authorities should develop implementable training programs and provide more learning opportunities for CDC p-lab staff, such as full-time education at university level or refresher training at a higher-level CDC ( 18 ). Staff shortages represent a grievous issue at the CDCs, which could be reasonably interpreted as a severe deficiency of staff funding with convincing evidence pointing to the directions of reforms for the introduction, motivation, and retention of laboratory personnel and technical talent.…”
Section: Discussionmentioning
confidence: 99%